Media augmented reality permainan tradisional Bali untuk meningkatkan motivasi belajar dan keterampilan biomotorik pada siswa sekolah dasar - Darmawan, Gede Eka Budi; Suranata, Kadek (Jurnal Konseling dan Pendidikan, 2025)
This study investigates the effectiveness of AR-based traditional Balinese games  as instructional tools for enhancing learning motivation and biomotor skills among elementary school students. Utilizing a pretest-posttest control group experimental design, 60 fifth-grade students were randomly allocated into experimental and control cohorts. The experimental group engaged in Physical Education, Sports, and Health (PJOK) sessions incorporating AR-based traditional Balinese games, while the control group received conventional PJOK instruction. Data were collected via validated learning motivation questionnaires and standardized biomotor skill assessments, with multivariate analysis of variance (MANOVA) employed for statistical analysis. Results demonstrated that the experimental group achieved a 25.3% increase in learning motivation and a 22.4% improvement in biomotor skills, both of which were statistically significant (p < 0.01) compared to the control group. These outcomes indicate that AR-based traditional Balinese games outperform conventional pedagogical methods in simultaneously enhancing cognitive engagement and physical competency. The study confirms the transformative potential of AR technology in primary education, particularly when aligned with culturally rooted content, to optimize holistic student development.